Swartzia hilaireana (Leguminosae), an “old” new species from the state of Minas Gerais, Brazil - Mansano, Vidal De Freitas; Falcão Junior, Marcus José De Azevedo; Torke, Benjamin M. (Phytotaxa, 2016)
Swartzia hilaireana, a new species of Swartzia sect. Swartzia from seasonal forests of the transition zone between cerrado and Altantic forest in Minas Gerais, Brazil, is described and illustrated. Although it was first collected nearly two centuries ago, only in recent decades has sufficient material of the species become available to make a confident taxonomic assessment. The species is closely related to S. pilulifera with which it may occur sympatrically, but it differs from that species in multiple aspects of its morphology.